1982
DOI: 10.2134/agronj1982.00021962007400060016x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Available Water as Influenced by Landscape Position and Aspect1

Abstract: In dryland farming, stored soil water is an essential source of water for crop production. The amount of water available for storage and crop use in a particular soil in hillslope topography is affected by its position on the landscape. The effect of slope aspect and position on soil water and its changes throughout the year in dryland farming were studied in southeast Nebraska. North, south, and east‐facing slopes of Wymore silty clay loam (Aquic Argiudolls fine, montmorillonitic mesic) were selected for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
11

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(84 citation statements)
references
References 10 publications
2
68
0
11
Order By: Relevance
“…These responses were also seen in similar harsh sites. For example, soils on north facing slopes on dryland in southeastern Nebraska had 20 % more water throughout the year than south facing slopes (Hanna et al, 1982). In a sandy grassland in Hungary, influence of carbon on nitrogen immobilization was more pronounced at sites where organic matter and water were lowest (Török et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These responses were also seen in similar harsh sites. For example, soils on north facing slopes on dryland in southeastern Nebraska had 20 % more water throughout the year than south facing slopes (Hanna et al, 1982). In a sandy grassland in Hungary, influence of carbon on nitrogen immobilization was more pronounced at sites where organic matter and water were lowest (Török et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that higher elevation soil sampling locations had lower ECa values compared to lower elevations due to higher volumetric water content at lower elevation positions. Hanna et al [50] observed soil moisture content during crop growth period using neutron probes and reported that within slope positions, soils on the foot slopes and backslopes contained on an average of 4 cm more …”
Section: Influence Of Topographic Position On Ecamentioning
confidence: 99%
“…Landscape position is another factor that will influence the efficiency of fall-applied N, through the accumulation of water in lower lying areas of the field (Hanna et al 1982). The effects of landscape position are most significant during the early spring period, when ponding of snowmelt runoff often occurs.…”
mentioning
confidence: 99%